Penguatan Kelembagaan dan Pemberdayaan Anak dalam Mewujudkan Kelurahan Layak Anak di Kelurahan Kotalama - Kemala Hasanah (Literasi Jurnal Pengabdian Masyarakat dan Inovasi, 2026)
This community service activity aims to strengthen institutional capacity and child empowerment in realizing a Kelurahan Layak Anak (KLA) in Kotalama, Malang City. The implementation consisted of two main stages: socialization of Malang City Regional Regulation Number 3 of 2024 concerning Child-Friendly Cities, and assistance in establishing the Children’s Forum and the KLA Task Force at the village level. A participatory approach was employed, involving 50 participants comprising 25 neighborhood representatives and 25 children aged 12–18 years. Participants actively engaged in discussions and deliberations to form and elect the management of child institutions. The results indicate an increased understanding among participants regarding KLA principles, particularly child participation and community roles in creating a child-friendly environment. The establishment of the Children’s Forum and the KLA Task Force serves as a concrete achievement and a shared commitment among the village government, community, and children to build a safe, inclusive environment that supports children's growth and development in Kotalama.